2011
DOI: 10.1007/s00402-011-1452-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three suture techniques and three suture materials on gap formation and failure load in ruptured tendons: a human cadaveric study

Abstract: These findings may be of relevance for the future clinical treatment of tendon ruptures. Further in vivo clinical application studies are desirable for the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…A cadaveric biomechanical study in the context of hamstring tendon rupture repair, which tested 3 suture materials and techniques, concluded that the Fiberwire-Baseball combination was most durable, whereas the Fiberwire-Kessler combination showed the lowest elongation after cyclic loading. 26 This study exemplifies the need for further research in tendon rupture repair efficacy. 11 An additional factor, aside from suture material and technique, is the repair attachment technique.…”
Section: Discussionmentioning
confidence: 70%
“…A cadaveric biomechanical study in the context of hamstring tendon rupture repair, which tested 3 suture materials and techniques, concluded that the Fiberwire-Baseball combination was most durable, whereas the Fiberwire-Kessler combination showed the lowest elongation after cyclic loading. 26 This study exemplifies the need for further research in tendon rupture repair efficacy. 11 An additional factor, aside from suture material and technique, is the repair attachment technique.…”
Section: Discussionmentioning
confidence: 70%
“…In a similar way, we looked for IL-1β and MMP-13 expression levels in all groups and found that both genes were highly expressed in tendons repaired with Ethibond Excel ® when compared with other suture material groups. (21). However, although these studies provide information about holding capacity and pull-out strength of different suture materials, all are in vitro studies and provide information only about instantaneous tensile strength at time zero.…”
Section: Discussionmentioning
confidence: 99%
“…The free end is then whip stitched for a distance of 30 mm with a high-resistance #2 suture ( Fig. 17.6 ), which has shown to withstand considerable maximum failure loads [ 25 ]. These sutures allow pulling from them in the next step; thus, commonly pulling with an aggressive Kocher forceps is avoided, and the tendon is not damaged.…”
Section: Harvest With a Closed Tendon Strippermentioning
confidence: 99%